Convergence of the θ-Euler-Maruyama method for a class of stochastic Volterra integro-diﬀerential equations - Samiha Mouchir; Abdeldjalil Slama (Journal of Numerical Analysis and Approximation Theory)
This paper addresses the convergence analysis of the θ-Euler-Maruyama method for a class of stochastic Volterra integro-diﬀerential equations (SVIDEs). At ﬁrst,  we discuss the existence, uniqueness,  boundedness and H¨older continuity of the theoretical solution. Subsequently, the strong convergence order of the θ-Euler-Maruyama approach for SVIDEs is shown. Finally, we provided numerical examples to illustrate the theoretical results.